Retrospective analysis of the control and prevention of tuberculosis among cattle in Ukraine in the period 1994–2020 - L. Y. Korniienko; A. V. Pyskun; V. V. Ukhovskyi; M. S. Karpulenko; O. A. Moroz; O. O. Pyskun; T. M. Tsarenko; G. B. Aliekseieva (Regulatory Mechanisms in Biosystems, 2021)
Bovine tuberculosis (bTB) – is a chronic infectious disease, the causative agent of which affects many species of mammals. It is a zoonosis caused by various types of mycobacteria in the complex Mycobacterium tuberculosis family Mycobacteriaceae. The most important etiological agent of bTB in cattle is M. bovis, which has been isolated from tuberculosis infected cattle for centuries. Livestock and species of the Bovidae family are the most susceptible to this pathogen and are the main reservoir species for animals and humans. In Ukraine, the main methods of diagnosing tuberculosis in animal husbandry are lifetime (clinical examination, allergic intradermal test with tuberculin), and postmortem techniques (pathological changes, bacteriological investigation). The authors performed a retrospective analysis of the epizootic situation of tuberculosis among cattle in Ukraine for the period 1994–2020 and conducted a critical assessment of the work done to prevent and control this disease. In total, over the last 27 years, 219 088 head of cattle with tuberculosis and 933 affected locations have been identified in Ukraine. The results of this work showed that in our country the epizootic situation of bovine tuberculosis on farms of various forms of ownership is fully controlled. The most active fight against tuberculosis was carried out during 1995–2015. In 1994–1997, the largest number of affected locations was registered, from 90 to 144, respectively, and the largest number of animals with tuberculosis – 21 395–33 474. In 1994–1995, the largest number of sick animals per one affected point was registered (371.9 and 471.7 head, respectively). Currently, official statistics show that many farms, especially in Vinnytska, Cherkaska and Kyivska regions, continue to show positive allergic reactions to tuberculin (46 898 reactions for the last 12 years). Applying diagnostic methods of research in complex (bacteriological, bioassay, molecular), excludes affection of cattle by pathogenic mycobacteria. This study showed that for the last 5 years no farms with confirmed pathological diagnosis by bacteriological methods have been registered and no culture of the pathogen from animals has been detected. Besides the scurpulous work of the veterinary service, in our opinion, the catastrophic decline in the number of cattle in Ukraine also had a significant impact on improving the epizootic situation regarding tuberculosis.